Flow injection potentiometric method based on Ce(IV)/Ce(III) redox reaction for determination of total antioxidant capacity - Puttaporn Klayprasert (2019)
© 2019, Chiang Mai University. All rights reserved. A simple and low-cost method for determination of total antioxidative capacity (TAC) was developed using a flow injection potentiometric method. The reaction involved the measurement of electrical potential change caused by the disturbance of Ce(IV)/Ce(III) ratio of a redox-reagent solution caused by the reduction of Ce(IV) to Ce(III) by the antioxidant. The optimum condition is as follow: reagent solution contained 0.06 mmol L-1 Ce(IV), 0.01 mmol LS Ce(III), and 0.5 mol L-1 H2SO4, and flow rate of solution of 0.8 mL min-1. A linear calibration graph was 0.08-1.00 mmol L-1 of ascorbic acid equivalent. The system provided good precision, i.e., %RSD (n=11) of 6.0, 1.4, and 4.1 for 0.08, 0.40 and 1.00 mmol L-1 ascorbic acid, respectively. The method was applied to evaluating TAC of tea infusion samples compared with the batch ceric reducing antioxidant capacity (CERAC) method and the batch ferric reducing antioxidant power (FRAP) method. Good correlation of the results between these methods was observed. The developed method is low cost, low reagent consumption, and low waste production. Moreover, it did not suffer from colored and colloidal substances presented in the samples.